2019
DOI: 10.1177/0907568219854518
|View full text |Cite
|
Sign up to set email alerts
|

Child rights governance: An introduction

Abstract: In this special issue, we explore child rights governance as the intersection between the study of governance and the study of children, childhood, and children’s rights. Our introduction puts forward a set of theoretical points of departure for the study of child rights governance, engaging with scholarship on human rights, international relations, history, and governance. It links the individual contributions to this special issue with four central dimensions of child rights governance, namely: temporality, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
14

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 60 publications
0
23
0
14
Order By: Relevance
“…In this respect, the CRC can be seen as the principal driving force behind a global culture of children's rights and an ever-increasing salience of children's rights in international and domestic politics. At the same time that efforts to implement children's rights domestically and internationally have accelerated, however, scholars have also started to question this (pre)dominance of matters of implementation in research on children rights, particularly a rather rigid and simple understanding of how international human rights standards are realized in domestic contexts (Holzscheiter et al 2019). The contemporary debate on children's rights among scholars and practitioners, which has largely been informed by Postcolonial and Critical Theory, also brings to light moments and processes of contestation and resistance to a powerful global discourse on appropriate childhood encapsulated in children's rights standards, questioning the easy traveling of seemingly universal values across time and space.…”
Section: Types Roles and Constellations Of Ios In Global Social Governancementioning
confidence: 99%
“…In this respect, the CRC can be seen as the principal driving force behind a global culture of children's rights and an ever-increasing salience of children's rights in international and domestic politics. At the same time that efforts to implement children's rights domestically and internationally have accelerated, however, scholars have also started to question this (pre)dominance of matters of implementation in research on children rights, particularly a rather rigid and simple understanding of how international human rights standards are realized in domestic contexts (Holzscheiter et al 2019). The contemporary debate on children's rights among scholars and practitioners, which has largely been informed by Postcolonial and Critical Theory, also brings to light moments and processes of contestation and resistance to a powerful global discourse on appropriate childhood encapsulated in children's rights standards, questioning the easy traveling of seemingly universal values across time and space.…”
Section: Types Roles and Constellations Of Ios In Global Social Governancementioning
confidence: 99%
“…In recent decades, systems of global governance have taken new forms that have particular implications for the analysis of global justice for children and youth (Holzscheiter et al, 2019). The traditional monopoly of national governments has been challenged, ushering in a 'dispersion' of authority and responsibility in global governance systems to include also transnational actors (TNAs) such as international nongovernmental organizations (INGOs), philanthropic foundations, scientific communities, and global corporations (Stroup & Wong, 2016;Tallberg et al, 2014).…”
Section: Three Contentious Casesmentioning
confidence: 99%
“…But as the struggle by, for example, young migrants demonstrates, highly influential principles of international law such as the best interests of the child (CRC Article 3) offer in practice relatively weak protections to remedy the injustices this group faces in terms of a lack of access to health, safety or a decent life (Josefsson, 2017a(Josefsson, , 2017b. On the contrary, these struggles show how, in the hands of a sovereign state (and its different legal and political bodies), child rights principles can be used to enforce other interests than those of children and youth in areas of migration, labour, climate, education and child protection (Holzscheiter et al, 2019). As children's rights scholars have repeatedly demonstrated, more implementation of children's rights principles is no guarantee for overcoming structural inequalities and oppression (Balagopalan, 2019;Nieuwenhuys, 2013;Reynaert et al, 2012).…”
Section: Empowered Inclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another example is discourse of children's rights. Recent studies have revealed that recognising young children as competent citizens and rights holders creates new forms of governance that respect their rights to be heard, to participate, and to have a voice in the decision-making process (Cohrssen & Page, 2016;Holzscheiter, Josefsson, & Sandin, 2019).…”
Section: Governmentality and Children Citizensmentioning
confidence: 99%